Targeting calciphylaxis: the emergence of vitamin K as a potential treatment - Maria Fusaro; Smeetha Sinha; Antonio Bellasi; Markus Ketteler; Carlo Alfieri; Martin H de Borst; Ditte Hansen; Pietro Manuel Ferraro; Juan Miguel Díaz-Tocados; Mathias Haarhaus; Mehmet Kanbay; Maurizio Gallieni; et al. (Clinical Kidney Journal, 2026)
Abstract Calciphylaxis, or calcific uraemic arteriolopathy (CUA), is a rare, life-threatening vascular disorder predominantly affecting patients with advanced chronic kidney disease (CKD), especially those on dialysis. It is characterized by arteriolar calcification, thrombosis, and painful ischemic skin lesions that frequently ulcerate, contributing to high morbidity and mortality. Calciphylaxis arises from medial arterial calcification, endothelial injury, and a pro-inflammatory, pro-thrombotic milieu. Disruption of vitamin K–dependent pathways, particularly impaired γ-carboxylation of matrix Gla protein (MGP), a potent inhibitor of vascular calcification, has emerged as a key mechanistic contributor. Functional vitamin K deficiency is common in CKD and is exacerbated by vitamin K antagonists such as warfarin, which markedly increase calciphylaxis risk. Observational studies show elevated levels of inactive MGP and other undercarboxylated Gla proteins in affected patients, linking vitamin K insufficiency to disease pathogenesis. Case reports and preliminary interventional studies suggest that vitamin K supplementation could restore MGP activity, reduce vascular calcification, and support wound healing, robust randomized controlled trial data are lacking. Ongoing trials, including the BEAT-Calci adaptive platform, aim to clarify the efficacy, optimal dosing, and safety of vitamin K as a targeted therapeutic strategy. Precision medicine approaches using vitamin K biomarkers and individualized anticoagulation may further improve outcomes. In conclusion, vitamin K–dependent pathways represent a promising mechanistic and potentially modifiable target in calciphylaxis. High-quality clinical trials are urgently needed to validate supplementation strategies and develop evidence-based, individualized management protocols for this severe condition.